MENINGKATKAN PENGETAHUAN DAN KESIAPAN IBU HAMIL DALAM MEMBERIKAN ASI EKSKLUSIF DI KLINIK NUSANTARA KESEHATAN - Tarigan, Yenni Gustiani; Roos Etty, Christina (JP2N : Jurnal Pengembangan Dan Pengabdian Nusantara, 2024)
The World Health Organization states that only two percent of babies experience Early Breastfeeding Initiation (EBI) and only around 40% of babies are given exclusive breast milk. Babies who are not given exclusive breast milk will tend to get sick easily. If the baby is sick, nutritional support will be disrupted because it is likely that the child will have difficulty eating, and this will result in malnutrition in toddlers. This community service activity aims to increase information and knowledge of pregnant women in the Medan Helvetia area about exclusive breastfeeding. This activity was carried out at the Nusantara Health Clinic, Medan Helvetia with the target participants being pregnant women. The instruments used in this activity were posters on how to care for breasts, practicing correct breastfeeding techniques and flyers about exclusive breastfeeding. The method used is counseling. As a result of the activity, there were 11 pregnant women who took part in the activity with the majority of mothers being aged 21-30 years and the majority with the highest education being high school. It is hoped that this activity can have a positive impact on pregnant women to be able to provide exclusive breast milk properly without providing any additional food until the baby is 6 months old. Keywords: Exclusive Breastfeeding, Pregnant Women, Promotion, Stunting